ARNOLD CHIARI MALFORMATION: SYMPTOMS, TYPES, AND TREATMENT (International conference on multidisciplinary science, 2023)
Arnold Chiari Malformation (ACM) is a complex neurological disorder characterized by structural defects in the base of the skull and the cerebellum. This article provides a comprehensive overview of ACM, including its symptoms, types, and treatment options. The symptoms of ACM can vary and affect various aspects of neurological functioning, including headaches, balance issues, and developmental delays. ACM is classified into four types, each with distinct characteristics and clinical presentations. Diagnosis involves a combination of medical history, physical examination, and imaging techniques. Treatment options range from conservative management to surgical interventions, depending on the severity of symptoms and neurological impairment. A multidisciplinary approach, including pain management and rehabilitation, is crucial for comprehensive care. Understanding the symptoms, types, and treatment options of ACM is essential for accurate diagnosis and optimal management of this condition.